(untitled) - Campbell, Neil A. (San Francisco, CA, 2007)
The Second Edition features dynamic new resources designed to focus students’ study time and help them master the most challenging topics in the course. New state-of-the-art eTutor animations and audio MP3 Tutor Sessions guide students through the most challenging topics in biology. A customized Study Plan on the accompanying website pinpoints exactly where students have trouble, and directs them to relevant sections of the text and media for help.
Keywords: Biology,Sinh học